Negotiating boundaries of care: an interpretative phenomenological analysis of the relational conflicts surrounding home mechanical ventilation following traumatic spinal cord injury. Issue 1 (1st January 2018) - Dickson, A.; Karatzias, T.; Gullone, A.; Grandison, G.; Allan, D.; Park, J.; Flowers, P.
ABSTRACT: Objectives: The aim of this study is to explore the phenomena of mechanical ventilation following traumatic spinal cord injury from three simultaneous perspectives; patients who require full-time mechanical ventilation ( n = 8), their informal family carers ( n = 8) and their formal carers ( n = 11). We focus upon the intra and inter- personal challenges of establishing boundaries within the triad. Design: Qualitative study. Methods: Semi-structured interviews were transcribed verbatim and analysed using interpretative phenomenological analysis (IPA). In order to encapsulate the inter-subjective, multi-dimensional and relational aspects of the experience, we focussed on recurrent themes which were independently reported across all three participant groups. Results: One major inter-connected recurrent theme was identified: 1) 'Negotiating boundaries of care and finding a "fit"'. It centres around establishing a 'line', or a boundary, which was imperative for retaining a sense of independence (for patients), a sense of home and privacy (for informal carers) and difficulties balancing complex care provision with the needs of family members so as not to cross that 'line' (for formal carers). Conclusions: The findings highlight the need for focussing on a 'fit' within the triad, balancing boundaries of care in order to establish a productive, satisfactory psycho-social environment for all three participant groups to live and/or work within. Recommendations for both future care provision and future research are suggested.